Unmet need to space and limit childbirth among reproductive age women in Pangkalpinang City, Bangka Belitung Province, Indonesia - Antarini, Antarini; Masfiah, Siti; Fitriani, Ayu; Junaidi, Lili (Yayasan Aliansi Cendekiawan Indonesia Thailand (Indonesian Scholars' Alliance), 2017)
Background: Population growth has become one of priority problems should be solved in almost all of developing countries, including Indonesia. Backward, Indonesia had successful family planning history. However, it shows decline figures nowadays. While, unmet need of family planning in several regions found increased. In 2007, unmet need was 8.6 %, inclined to 11.4% in 2015, which is consisted of 4.5% for spacing children and 8.6% for limiting children. Social demography, economic, access to health services, family support and perception revealed have the contribution to unmet need. Aims: This study aimed to explore unmet need family planning due to birth spacing and limiting situation among reproductive age women in Pangkal Pinang City, Bangka Belitung Province.Methods: This study was an explanatory research used cross-sectional design. The population was women of childbearing age who experienced unmet need of family planning in Pangkal Pinang, 2016. 98 women were taken by proportional random sampling to participate in this study.Results: Research showed that the most of the unmet need for family planning were among 25-29 years old women. About two third (66.3%) of unmet need women occurred due to the willingness to space the childbirth and 33.7% willing to limit the childbirth. Birth spacing tended to be favored by young mothers, early marriage (1-5 years old), had low parity and had low education attainment. Whilst, limiting childbirth tended to be preferred by women with lenght marriage experience (>15 years old), had high parity, older mothers, and middle education level (senior high school) attainment. Conclusion: Both of spacing and limiting have no difference according to the economic situation, all of them mostly were the household wife from low-income family. Husband support to do not use contraception were found in both birth spacing and birth limiting. The study suggest to provincial health office and national family planning coordination board that family planning program should not just involve the wife, but husband as well due to their high influence in family planning decision. Keyword: Unmet need, family planning, birth spacing and limiting